Peroxisome Proliferator Activated Receptors and Lipoprotein Metabolism - Sander Kersten (PPAR Research)
Plasma lipoproteins are responsible for carrying triglycerides and cholesterol in the blood and ensuring their delivery to target organs. Regulation of lipoprotein metabolism takes place at numerous levels including via changes in gene transcription. An important group of transcription factors that mediates the effect of dietary fatty acids and certain drugs on plasma lipoproteins are the peroxisome proliferator activated receptors (PPARs). Three PPAR isotypes can be distinguished, all of which have a major role in regulating lipoprotein metabolism. PPARα is the molecular target for the fibrate class of drugs. Activation of PPARα in mice and humans markedly reduces hepatic triglyceride production and promotes plasma triglyceride clearance, leading to a clinically significant reduction in plasma triglyceride levels. In addition, plasma high-density lipoprotein (HDL)-cholesterol levels are increased upon PPARα activation in humans. PPARγ is the molecular target for the thiazolidinedione class of drugs. Activation of PPARγ in mice and human is generally associated with a modest increase in plasma HDL-cholesterol and a decrease in plasma triglycerides. The latter effect is caused by an increase in lipoprotein lipase-dependent plasma triglyceride clearance. Analogous to PPARα, activation of PPARβ/δ leads to increased plasma HDL-cholesterol and decreased plasma triglyceride levels. In this paper, a fresh perspective on the relation between PPARs and lipoprotein metabolism is presented. The emphasis is on the physiological role of PPARs and the mechanisms underlying the effect of synthetic PPAR agonists on plasma lipoprotein levels.